(NmAKEDONSKIJ QZYK (B:s (Nu^EBNOE POSOBIE (B/s - (NkOWALEW(B, (Nn(B.(Ns(B.s ((NmOSKWA (B:s (NiZD(B-(NWO iWANOWSKOGO GOS(B. (NUN(B-(NTA(B,s, 1977)
(NsPISOK LIT(B. (NS(B. 599s
(NuKAZ(B. (NIMEN(B: (NS(B. 600-606s
Keywords: (NrUSSKIJ QZYK (B- (NgRAMMATIKAs; (NsLOWO W RUSSKOM QZYKEs